Evaluation of neonatal and maternal morbidity in mothers with gestational diabetes: a population-based study - Domanski, Grzegorz (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Gestational diabetes mellitus (GDM) is the most frequent complication during pregnancy. Untreated GDM is a severe threat to maternal and neonatal health. Based on recent evidence, up to 15% of all pregnancies may be affected by GDM. We hypothesized that in a rural birth cohort, higher maternal BMI and adverse socioeconomic conditions would promote GDM, which in turn would lead to adverse effects on pregnancy outcomes. METHODS: The current study is a part of a population-based cohort study examining the health and socioeconomic information from 5801 mothers and their children. The study, titled the Survey of Neonates in Pomerania (SNiP), was based in northeastern Pomerania, Germany (2002–2008). RESULTS: The cumulative incidence of GDM was 5.1%. Multiple logistic regression revealed prepregnancy overweight (OR 1.84 (95% CI 1.27–2.68)), prepregnancy obesity (OR 3.67 (2.48–5.44)) and maternal age (OR 1.06 (1.03–1.08)) as risk factors for GDM (p = 0.001). Alcohol use during pregnancy (OR 0.61 (0.41–0.90), a higher monthly income (OR 0.62 (0.46–0.83)), and the highest level of education (OR 0.44 (0.46–0.83)) decreased the risk of GDM. Newborns of GDM mothers had an increased risk of hypoglycaemia (OR 11.71 (7.49–18.30)) or macrosomia (OR 2.43 (1.41–4.18)) and were more often delivered by primary (OR 1.76 (1.21–2.60)) or secondary C-section (OR 2.00 (1.35–2.97)). Moreover, they were born 0.78 weeks (95% CI -1.09 – -0.48 weeks) earlier than infants of mothers without diabetes, resulting in higher percentage of late preterm infants with a gestational age of 32–36 weeks (11.1% vs. 6.96%). CONCLUSIONS: Age and BMI before pregnancy were the predominant mediators of the increased risk of GDM, whereas a higher income and educational level were protective. GDM affected relevant perinatal and neonatal outcomes based on its association with an increased risk of delivery by C-section, preterm birth, macrosomia at birth and neonatal hypoglycaemia.